Odpowiedzi

  • Użytkownik Zadane
2010-02-11T21:27:55+01:00
3 x + 9 = - 3 x + 9 /+ 3x
6x +9 = 9 /-9
6x= 0
x=0

- 27 + 1 = 2 x + 59
-26= 2x +59 /-59
-85 = 2x
x= -42,5

45 x - 19 = 19 x - 45/+19
45x= 19x -26 /-19x
26x = -26 / :26
x= -1

82 x - 9 = - 18 x + 1 /+9
82x =-18x +10 /+18x
100x= 10 /:100
x= 0,1
1 5 1
  • Użytkownik Zadane
2010-02-11T21:28:11+01:00
3 x + 9 = - 3 x + 9
9-9=--3x-3x
x=0

- 27 + 1 = 2 x + 59
26-59=2x
-33=2x/:-33
x=-16,5

45 x - 19 = 19 x - 45
45x-19x=-45+19
26x=-26/:26
x=-1

82 x - 9 = - 18 x + 1
82x+18x=1+9
100x=10/:100
x=0,1
1 5 1